Study on the effect of fuel additive on PFI gasoline engine performance and emissions - Huo Yongzhan; Jing Xiaojun; Yin Zenghui; Wu Mingding (E3S Web of Conferences, 2022)
With increasingly stringent emission and fuel consumption regulations, fuel additives have been proved to have a huge role in energy conservation and emission reduction, a new type of fuel additive based on nitroparaffin has received worldwide attention. An experimental study was conducted with the aim of developing an understanding of the fuel additive’s effect on a 1.5L naturally aspirated PFI gasoline engine’s power performance, fuel economy, emissions and cylinder cleanliness. The results show that when fueled with fuel additive, engine power increased at full load condition. The commonly used working condition’s average fuel consumption decreased by 4.5% at fuel consumption contour map. For pollutant emissions, unburned hydrocarbons (HC), smoke (filter smoke number, FSN) decreased significantly, slightly higher nitrogen oxides (NOx) compared with no fuel additive. Furthermore, the use of fuel additive has a positive effect on elimination of carbon deposit in the cylinder.